Konsumsi Energi dan Pembangunan Ekonomi di Asia Tenggara - Rezki, Jahen Fachrul (Jurnal Ekonomi dan Pembangunan Indonesia, 2011)
Economic development in the South East Asia, which is at the stage of industrialization, has high dependency on energy consumption. This paper examines the relationship between energy consumption and economic development in the region. Using cross-sectional data, this study find the relationship between energy demand and per capita GDP, population and industrial share of output. Oil contributes 80% to energy consumption followed by electricity and natural gas. The result also shows no evidence of relationship between economic crisis and energy consumption. It suggest diversification of energy use and promoting more efficient alternative energy source to increase economic growth.